2016
DOI: 10.1371/journal.pone.0145894
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acute Dopamine Precursor Depletion on the Reinforcing Value of Exercise in Anorexia Nervosa

Abstract: This study investigated whether dopaminergic systems are involved in the motivation to engage in behaviours associated with anorexia nervosa (AN), specifically, the drive to exercise. Women recovered from AN (AN REC, n = 17) and healthy controls (HC, n = 15) were recruited. The acute phenylalanine/tyrosine depletion (APTD) method was used to transiently decrease dopamine synthesis and transmission. The effect of dopamine precursor depletion on drive to exercise was measured using a progressive ratio (PR) exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Individuals with AN demonstrate elevated skin conductance, decreased eye blink startle, and increased electroencephalogram late positive potential in response to underweight stimuli (Clarke, Ramoz, Fladung, & Gorwood, ; Horndasch et al, ; O'Hara et al, ), indicating greater salience and PA responding. This altered dopaminergic functioning and reward response is corroborated by a study showing increased eye blink startle in response to thinness images following dopamine depletion (O'Hara et al, ).…”
Section: Current Evidencementioning
confidence: 68%
“…Individuals with AN demonstrate elevated skin conductance, decreased eye blink startle, and increased electroencephalogram late positive potential in response to underweight stimuli (Clarke, Ramoz, Fladung, & Gorwood, ; Horndasch et al, ; O'Hara et al, ), indicating greater salience and PA responding. This altered dopaminergic functioning and reward response is corroborated by a study showing increased eye blink startle in response to thinness images following dopamine depletion (O'Hara et al, ).…”
Section: Current Evidencementioning
confidence: 68%
“…In accord with this hypothesis, a recent study showed that decreasing DA (via APTD) did not reduce motivation to exercise in AN REC, but did so in HC. This suggests that drive to exercise develops into a behaviour that is independent of DA-mediated reward processes and may become dependent on corticostriatal neurocircuitry that regulates automated, habit-like behaviours [ 63 ]. Therefore, in the present study, diminished reflexive startle response to underweight and exercise cues in AN REC during BAL (but not during APTD) suggests that, unlike HC, these individuals reflexively appraise such cues as more rewarding and that this is partly DA-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of the neural network involved in reward, punishment, and motivational processes is also described in ED patients [40,53]. Several studies have shown that dopamine system disturbance contributes to the development and maintenance of AN and other EDs [54,55].…”
Section: Neurobiological Regulationmentioning
confidence: 99%